2021
DOI: 10.3390/atmos12121561
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of X-Band Radar for Extreme Events in a Spatially Complex Precipitation Region in North Peru: Machine Learning vs. Empirical Approach

Abstract: Cost-efficient single-polarized X-band radars are a feasible alternative due to their high sensitivity and resolution, which makes them well suited for complex precipitation patterns. The first horizontal scanning weather radar in Peru was installed in Piura in 2019, after the devastating impact of the 2017 coastal El Niño. To obtain a calibrated rain rate from radar reflectivity, we employ a modified empirical approach and draw a direct comparison to a well-established machine learning technique used for rada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The results of flood routing for the La Leche basin, as shown in Figure 8, also indicate an increase in flow in an east to southwest direction as the return period progresses. This pattern is characteristic of the North Pacific basins of Peru, as reported by the investigations of Arriola et al (2021), Rollenbeck et al (2021) and Arriola et al (2023). Furthermore, this sequence of hydrological behavior has been influenced in recent years by extreme events due to the El Niño Phenomenon (Aguirre et al, 2019;Carrizales et al, 2022;Peña et al, 2023).…”
Section: Resultsmentioning
confidence: 54%
“…The results of flood routing for the La Leche basin, as shown in Figure 8, also indicate an increase in flow in an east to southwest direction as the return period progresses. This pattern is characteristic of the North Pacific basins of Peru, as reported by the investigations of Arriola et al (2021), Rollenbeck et al (2021) and Arriola et al (2023). Furthermore, this sequence of hydrological behavior has been influenced in recent years by extreme events due to the El Niño Phenomenon (Aguirre et al, 2019;Carrizales et al, 2022;Peña et al, 2023).…”
Section: Resultsmentioning
confidence: 54%
“…Equation (12) calculates the precision of a model. The precision measures the proportion of correct positive predictions.…”
Section: Model Evaluationmentioning
confidence: 99%
“…Previous studies have suggested that machine learning can be effective in this field, but it is still relatively new, particularly in the development of hybrid machine learning models. Rollenbeck et al [12] showed that machine learning can outperform empirical approaches in calibrating X-band radar for extreme weather events in a region of complex precipitation in North Peru, highlighting the potential of advanced algorithms in such scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…In the global context, where climate change is exacerbating water-related challenges, the use of technologies such as remote sensing and geographic information systems (GIS) plays a critical role in adapting to and mitigating extreme events [32][33][34][35]. Remote sensing provides detailed insights into key hydrological variables like rainfall, evapotranspiration, and wetland extent [36,37].…”
Section: Introductionmentioning
confidence: 99%